Nicorandil preserves blood-brain barrier and improves memory impairment in hypertensive rats - YEGEN, BERRAK; ERTAŞ, BÜŞRA; ŞENER, GÖKSEL; KOYUNCUOĞLU, TÜRKAN (MARMARA UNIV, 2019)
In renovascular hypertension (RVH), oxidative stress and inflammation due to high blood pressure and elevated levels of angiotensin 2 are mainly responsible of cerebrovascular complications and impaired cognitive functions. Since the nicorandil has been shown to exert neuroprotective, anti-inflammatory and antioxidant effects, we investigated the effect of nicorandil against vascular dementia and blood brain barrier damage in a rat model of angiotensin-dependent hypertension. Wistar albino rats, were divided as sham-operated control, renovascular hypertension (RVH) and Nicorandil-treated RVH groups. Silver clip was implanted onto the left renal artery. Using the tail-cuff method, blood pressure of rats was measured before the surgery and at the end of the post-surgical 3rd and 12th weeks. Nicorandil (4mg/kg, orally) or vehicle was administered for 9 weeks. Twelve weeks after RVH surgery, a new object recognition test was performed. Following the determination of blood brain barrier integrity, serum samples were taken for the evaluation of proinflammatory cytokines tumor necrosis alpha (TNF-alpha) and interleukin-1 beta (IL-1 beta). Levels of sodium-potassium adenosine triphosphatase (Na+/K+-ATPase), as a marker of endothelial damage, were evaluated in the hippocampal tissues. RVH resulted in significant increases in TNF-alpha and IL-1 beta levels and decreases in Na+/K+-ATPase levels, along with impairment in blood brain barrier integrity and memory performance. In the nicorandil treatment group, these indices were reversed back to control levels. The present data demonstrated that nicorandil attenuates RVH-induced memory impairment and blood brain barrier damage in rats with RVH.
Keywords: Renovascular hypertension; angiotensin 2; nicorandil; blood brain barrier; vascular dementia; II-INDUCED HYPERTROPHY; NF-KAPPA-B; RHO-KINASE; PERMEABILITY; INFLAMMATION; SUPEROXIDE; ACTIVATION; EXPRESSION; RECEPTOR; STIMULATION